Respiratory outcomes of metformin use in patients with type 2 diabetes and chronic obstructive pulmonary disease - Yen, Fu-Shun (Sci Rep, 2020)
Few studies investigated the respiratory outcomes of metformin use in patients with coexistent type 2 diabetes mellitus (T2DM) and chronic obstructive pulmonary disease (COPD). We want to compare the long-term respiratory endpoints of metformin use and nonuse in patients with T2DM and COPD. This retrospective cohort study enrolled patients with T2DM and COPD from Taiwan’s National Health Insurance Program between January 1, 2000, and December 31, 2012. Main outcomes were hospitalized bacterial pneumonia, hospitalization for COPD, noninvasive positive pressure ventilation (NIPPV), invasive mechanical ventilation (IMV), and lung cancer. In total, 20,644 propensity score-matched metformin users and nonusers were assessed. The adjusted hazard ratios (95% confidence intervals) of metformin use relative to nonuse for bacterial pneumonia, hospitalization for COPD, NIPPV, IMV, and lung cancer were 1.17 (1.11–1.23), 1.34 (1.26–1.43), 0.99 (0.89–1.10), 1.10 (1.03–1.17), and 1.12 (0.96–1.30). Metformin use also exhibited significant dose–response relationship with respect to the risks of bacterial pneumonia, hospitalization for COPD and IMV. Consistent results were found in the sensitivity test. This nationwide cohort study demonstrated that in patients with T2DM and COPD, metformin use was associated with higher risks of pneumonia, hospitalization for COPD, and IMV. If patients with COPD use metformin, vigilance with regard to their pulmonary condition may be required.